Graceful labeling construction for some special tree graph using adjacency matrix - Nikson Simarmata; Ikhlas Pratama Sandy; Kiki A. Sugeng (Electronic Journal of Graph Theory and Applications (EJGTA), 2023)
In 1967, Rosa introduced β − labeling which was then popularized by Golomb under the name graceful. Graceful labeling on a graph G is an injective function f : V(G)→{0, 1, 2, …, |E(G)|} such that, when each edge uv ∈ E(G) is assigned the label |f(u)−f(v)| the resulting edge labels are distinct. If graph G has graceful labeling then G is called a graceful graph. Rosa also introduced α − labeling on graph G which is a graceful labeling f with an additional condition that there is λ ∈ {1, 2, …, |E(G)|} so that for every edge uv ∈ E(G) where f(u)<f(v) then f(u)≤λ < f(v). This paper gives a new approach to showing a graph is admitted α − labeling using an adjacency matrix. Then this construction will be used to construct graceful labeling for the superstar graph. Moreover, we give a graceful labeling construction for a super-rooted tree graph.